Tax Policy and Muslim Consumer Behavior: Evidence from Indonesia’s Retail Sector - Suhendar, Suhendar; Evi Ekawati; Yoyo Arifardhani; Dewi, Hayuningtyas Pramesti; Dahlan, Ahmad; Hamdan, Muhammad Sirajuddin Qahtan (Economica: Jurnal Ekonomi Islam, 2023)
Indonesia’s retail sector faces challenges adapting to recent VAT policy changes amid ongoing recovery from the COVID-19 downturn. This study examines the relationship between the VAT rate increase—from 11% to 12% in April 2022—and consumer purchasing power, using a mixed-methods approach grounded in Islamic ethics. Conducted across five major Indonesian cities, the analysis reveals that the tax increase has spurred improvements in financial planning, with 78% of respondents reporting more structured shopping behavior. Consumer adaptation strategies—including digital tools and loyalty programs—resulted in 15–20% savings. Demand elasticity varied by product type: essential goods showed low elasticity (-0.3), while non-essentials exhibited higher elasticity (-1.2), reflecting consumer prioritization. The retail sector demonstrated resilience, growing from 3.2% to 4.2%, with operational efficiency rising from 82% to 88% and digital transformation reaching 87%. These findings offer empirical support for the positive effects of fiscal adjustments and highlight the role of Islamic ethics in promoting prudent, purposeful consumption.